2016
DOI: 10.1002/pen.24358
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of carbon nanotubes containing segmented polyurethane elastomer

Abstract: Nanocomposites of the segmented polyurethane (SPU) elastomer with different concentrations of multiwall carbon nanotubes (MWCNTs) have been prepared. Scanning electron microscopy has been used to visualize the surface morphology and distribution of the nanotubes inside the matrix. Differential scanning calorimetry has been utilized to investigate the effects of MWCNTs on the crystallization characteristics of the SPU by collecting data at four cooling rates namely 5, 10, 15, and 20°C/min in the temperature ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Moreover, the crystallinity of the TPU/MWCNT nanocomposites has been noticeably increased comparing pristine TPU due to positive nucleating effect of MWCNTs. Gupta et al have reported that incorporation of the MWCNTs into the PU matrix increases the onset and peak temperatures of crystallization, whereas decreases the activation energy of the nanocomposites due to heterogeneous nucleation effect of the MWCNTs . Song et al have proposed that the incorporation of clay nanoplates into the PU matrix decreases the size of the spherical aggregates, corroborating the key role of clay nanoplates on the aggregation performance of the hard domains …”
Section: Introductionmentioning
confidence: 93%
“…Moreover, the crystallinity of the TPU/MWCNT nanocomposites has been noticeably increased comparing pristine TPU due to positive nucleating effect of MWCNTs. Gupta et al have reported that incorporation of the MWCNTs into the PU matrix increases the onset and peak temperatures of crystallization, whereas decreases the activation energy of the nanocomposites due to heterogeneous nucleation effect of the MWCNTs . Song et al have proposed that the incorporation of clay nanoplates into the PU matrix decreases the size of the spherical aggregates, corroborating the key role of clay nanoplates on the aggregation performance of the hard domains …”
Section: Introductionmentioning
confidence: 93%
“…Gupta et al have reported that nucleation effect of the MWCNTs into the polyurethane matrix increases the onset and peak temperatures of crystallization .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extremely high surface area in nanocomposites, an improvement of the mechanical, barrier and thermo-mechanical properties, and conductivity can be achieved at low filler contents which marks the main advantage of these materials over the microphase reinforced composites (less than 5 wt%) [8][9][10]. Crystallization behavior of polymer such as nucleation rate, crystallite size, crystallization temperature, and rate of crystal formation are altered by the presence of nanofillers [11,12]. Most of the relative crystallinity analyses are based on the Avrami equation which can describe the kinetics of polymer crystallization.…”
Section: Introductionmentioning
confidence: 99%